MICROBIOLOGICAL ASSESSMENT OF ANTIBIOTIC-RESISTANT BACTERIA ISOLATED FROM CLINICAL SAMPLES: IMPLICATIONS FOR PUBLIC HEALTH AND RATIONAL ANTIMICROBIAL THERAPY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Antibiotic resistance has emerged as one of the most pressing challenges in modern microbiology and clinical medicine. The rapid evolution of resistant bacterial strains threatens the effectiveness of antimicrobial therapy and increases morbidity, mortality, and healthcare costs worldwide. This study aimed to isolate pathogenic bacteria from clinical samples, identify them using standard microbiological techniques, and evaluate their susceptibility to commonly used antibiotics. A total of 75 biological specimens were analyzed using culture-based, staining, and biochemical methods. Antibiotic susceptibility testing was performed using the Kirby–Bauer disk diffusion method. The results demonstrated a high prevalence of multidrug-resistant strains, particularly among Gram-negative bacteria. The findings highlight the necessity of continuous microbiological surveillance, rational antibiotic use, and implementation of antimicrobial stewardship programs to control the spread of resistance.